2004
DOI: 10.1038/sj.sc.3101538
|View full text |Cite
|
Sign up to set email alerts
|

Gross quantitative measurements of spinal cord segments in human

Abstract: Study design: Anatomical measurement. Objective: To obtain quantitative anatomical data on each spinal cord segment in human, and determine the presence of correlations between the measures. Setting: Department of Rehabilitation Medicine, Pusan National University Hospital, Pusan, Korea. Methods: A total of 15 embalmed Korean adult human cadavers (13 males, two females; mean age 57.3 years) were used. The length of each cord segment was defined as the root attachment length plus the upper inter-root length. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(143 citation statements)
references
References 16 publications
8
129
0
2
Order By: Relevance
“…In the rat, however, the hindlimb muscles are innervated by a longer motor pool spread throughout more spinal cord segments than in humans. 31,34 The H-reflex confirms the presence of an upper motor neuron injury in this model, which is well described throughout the human and animal literature. 22 We observed significant at-level sensory alterations after clip impact-compression injury, which mimics similar outcomes seen in many lumbar root avulsion models.…”
Section: Neurobehavioral Recoverysupporting
confidence: 57%
“…In the rat, however, the hindlimb muscles are innervated by a longer motor pool spread throughout more spinal cord segments than in humans. 31,34 The H-reflex confirms the presence of an upper motor neuron injury in this model, which is well described throughout the human and animal literature. 22 We observed significant at-level sensory alterations after clip impact-compression injury, which mimics similar outcomes seen in many lumbar root avulsion models.…”
Section: Neurobehavioral Recoverysupporting
confidence: 57%
“…The spinal cord was contoured as a structure approximately 7 mm in diameter, contained centrally within the bony limits of the spinal canal. The contoured cord was designed to reflect the average cord size of our previous ten radiosurgery spine patients who were planned using fusion of MRI or CT myelogram as well as measurements reported in the literature 9. To ensure comparability, each contour and image set was communicated unaltered from Eclipse to each of the other treatment planning systems through DICOM‐RT.…”
Section: Methodsmentioning
confidence: 99%
“…Any of these factors could explain the observed differences between our study and that of Grande et al 8 While the myelograms obtained during this study do not allow visualization of the spinal cord, previous research has demonstrated that the diameter of the human spinal cord at T-10 ranges from about 5 mm to about 9.5 mm in the transverse plane and from about 4 mm to about 8.5 mm in the sagittal plane. 17 The minimal canal width measured in this study (7.73 mm after closure of the VCR) is within a range that may leave insufficient room for the spinal cord and could result in damage to the spinal cord itself. Although saline was injected into the thecal sac to simulate CSF in our model, such an approximation fails to account for the dynamic CSF pulsations seen in vivo.…”
mentioning
confidence: 93%